Preparation and characterization of surface-modified PLGA-polymeric nanoparticles used to target treatment of intestinal cancer. (17th February 2018) - Ahmad, Niyaz; Alam, Md Aftab; Ahmad, Rizwan; Naqvi, Atta Abbas; Ahmad, Farhan Jalees
Abstract: Docetaxel (DTX), a cytotoxic taxane, is a poor water-soluble drug and exhibits less oral bioavailability. Current research investigates the effective transport, for DTX-loaded chitosan (CS)-coated-poly-lactide- co -glycolide (PLGA)-nanoparticles (NPs) (DTX-CS-PLGA-NPs) and DTX-PLGA-NPs as well as a novel third-generation P-gp inhibitor i.e. GF120918 (Elacridar), across intestinal epithelium with its successive uptake by the tumour cells in an in vitro model. The prepared NPs showed a spherical shape particle size i.e. <123.96 nm with polydispersity index (PDI) of <0.290 whereas for CS-coated NPs, the zeta potential was converted from negative to positive value along with a small modification in particle size distribution. The entrapment efficiency observed for DTX-CS-PLGA-NPs was 74.77%, whereas the in vitro release profile revealed an initial rapid DTX release followed by a sustained release pattern. For apparent permeability, DTX-CS-PLGA-NPs and DTX-PLGA-NPs along with GF120918 showed a five-fold ( p  < .01) and 2.2-fold enhancement, respectively, as observed in rat ileum permeation study. Similarly, for pharmacokinetic (PK) studies, higher oral bioavailability was observed from DTX-CS-PLGA-NPs (5.11-folds) and DTX-PLGA-NPs (3.29-folds) as compared with DTX-suspension (DTX-S). Cell uptake studies on A549 cells as performed for DTX-CS-PLGA-NPs and DTX-PLGA-NPs loaded with rhodamine 123 dye, exhibited enhanced uptake as compared with plain dye solution. The enhanced uptake for DTX-CS-PLGA-NPs and DTX-PLGA-NPs formulations in the presence of GF120918 was confirmed further with the help of confocal laser scanning microscopic images (CLSM). The potential of the third-generation novel P-gp inhibitor (GF120918) investigated for the effective delivery of DTX as well as investigation of permeability and uptake studies whereby a strong potential of GF120918 for effective oral delivery was established.